804 A phase II study of the anti-programmed cell death-1 (PD-1) antibody penpulimab in patients with metastatic nasopharyngeal carcinoma (NPC) who had progressed after two or more lines of chemotherapy. (9th November 2020) - Chen, Xiaozhong; Wang, Wei; Zou, Qingfeng; Li, Jingao; Hu, Chaosu; Hu, Chaosu; Lin, Qin; Zhu, Xiaodong; Jiang, Yi; Sun, Yan; Shen, Liangfang; Wang, Lin; et al.
Abstract : Background: NPC is rare but has a distinct geographic distribution, with a predominance in Southeast Asia. Favorable results with PD-1 inhibitors in NPC provide a strong rationale to investigate penpulimab in this disease. Penpulimab was engineered to eliminate FcγR binding and ADCC/ADCP completely, where ADCC/ADCP effects can induce T-cell apoptosis and clearance and then compromise anti-tumor activity. Penpulimab demonstrated a slower PD-1 antigen binding off-rate than marketed PD-1 antibodies, which result in better cellular activity and higher receptor occupancy. Penpulimab also showed numerous contacts with N58 glycosylation on the BC loop of PD-1 which could be an advantage to facilitate interaction of PD-1 antibody and may contribute to slower binding off-rate. These structural differentiations offer more robust biological effect and enhance anti-tumor activity of penpulimab. Methods: AK105-202 (NCT03866967 ) is a multicenter, single-arm, open-label study of penpulimab in metastatic NPC patients (pts) with disease progression after ≥2 prior lines of therapy including platinum-containing chemotherapy. All patients received penpulimab 200 mg q2w until progression or unacceptable toxicity. The primary endpoint was ORR based on RECIST v1.1 as assessed by an independent review committee (IRC). Key secondary endpoints included DCR, PFS, duration of response (DoR). Archived tissues were retrieved for the analysis of PD-L1 (Shuwen SAB-028). PD-L1 expression of tumor proportion score (TPS)≥50% was regarded as positive. Plasma Epstein-Barr virus DNA were obtained for biomarker correlative analysis. Results: As of 18 September 2020, the median follow-up was 7.9 months (range 0.9 to 16.9). The anti-tumor activity of penpulimab in the 111 pts with disease progression after ≥2 prior lines of therapy evaluable for efficacy (defined as pts who had an opportunity to be followed for at least 16 weeks and had measurable disease at baseline per RECIST v1.1) is shown in the table 1 . Treatment-related adverse events (TRAEs, including unlikely related) occurred in 79.2% of pts (≥G3 in 14.6% [19/130], treatment discontinuation in 3.1% [4/130]). Treatment-related SAEs occurred in 10.0% [13/130]. Most frequent TRAEs (≥10%) were fever (24.5%), hypothyroidism (24.6%), anemia (23.1%), ALT increased (17.0%) and WBC decreased (10.8%). Grade ≥3 TRAEs (≥2%) were hepatic function abnormal (2.3%) and anemia (2.3%). Conclusions: Penpulimab demonstrated encouraging anti-tumor activity and favorable safety profile in pts with disease progression after ≥2 prior lines of therapy. A higher proportion of objective responses was observed in NPC pts with PD-L1–positive tumors receiving penpulimab than those with PD-L1–negative tumors.